THE ORTHODOX CHURCH IN THE JAWS OF ACTUAL GLOBAL GEOPOLITICAL CHANGES : Српски - Devrnja, Zoran (National interest, 2024)
This paper points to processes that have been going on for a century and aim to change the modern image of the Orthodox Church. One patriarchy, the first in honour, is trying to impose itself as the supreme interpreter of traditions and theological narratives, as well as to change the canonical structure and ecclesial identity of all other autocephalous Orthodox Churches. The prehistory of the devastating processes starts with the restoration of national and church self-consciousness in the 19th century in the Balkans, which led to the emergence of the brainchild of restoring the autocephalous status of church communities in the liberated territories. The procedures for church independence were not initially approved by the Patriarchate of Constantinople. The leading patriarchate in honour, faced with the actual church situation on the Balkan Peninsula, confirmed the independence of the Athens Archdiocese and the Metropolitanate of Belgrade in the second half of the 19th century. However, the 20th century brought massive changes. The Balkan Wars, the Great War, the communist revolution in Russia, the disappearance of the Ottoman and Austrian empires, and the great tragedy of the Orthodox Greeks in Constantinople and Asia Minor led to changes in theological paradigms in the Patriarchate of Constantinople, which also initiated a change in its church position from Primus inter pares (The first among equals) to Primus sine paribus (The first without equals). This fact leads to the pretensions of this patriarchate to the entire Orthodox diaspora, as well as to the exclusive right to form criteria for granting autocephalous status to church communities that request it. However, the representatives of the Patriarchate of Constantinople very consistently continue to develop the theological assumptions of the new ecclesiological matrix, especially in the decades after the Second World War. Quite consciously and with the expected outcome, they are approaching the levers of power of the US political elite with the desire to strengthen their position in front of the repressive regime in Turkey. Soon, they began to use the established connections and increased political potential to impose their ecclesiological and canonical views on other Orthodox churches, especially since the fall of the Iron Curtain and the demolition of the Berlin Wall. The resistance of the new ecclesiological narratives of the Patriarchate of Constantinople, which give it a priority place in relation to all other churches and in the processes of accomplishing canonical and spiritual authority, not just honour, to all reasoned theological and historical criticism from Orthodox theologians, canonists, and archbishops, points to the fact that the theological turnover of this Patriarchate is well and studiously prepared. It is apparent that this church expects essential benefits from it, but also that the shaped narratives have a reflective effect on anticipated political situations that have been preparing for decades under the guise of the pseudo-ideological supremacy of the West. Since it is under massive transformative pressure from the Western power centres, it’s evident that the Orthodox Church is in great turmoil, with painful uncertainty about its resolution. The processes that are mentioned are part of global geopolitical change. Rational interpretation of reality suggests they are synchronized from the same centre of power and political decision-making, as well as mutually compatible and complementary. This fact tells us that the mutual relations of the Orthodox churches are in a crisis that seems to be designed and managed for the purpose of more comprehensive intervention in the self-consciousness of the Orthodox peoples and their ecclesial, national, ethical, and political identity.